2015
DOI: 10.1128/aac.04694-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Trypanosoma cruzi Sirtuins as Possible Drug Targets for Chagas Disease

Abstract: c Acetylation of lysine is a major posttranslational modification of proteins and is catalyzed by lysine acetyltransferases, while lysine deacetylases remove acetyl groups. Among the deacetylases, the sirtuins are NAD ؉ -dependent enzymes, which modulate gene silencing, DNA damage repair, and several metabolic processes. As sirtuin-specific inhibitors have been proposed as drugs for inhibiting the proliferation of tumor cells, in this study, we investigated the role of these inhibitors in the growth and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(105 citation statements)
references
References 64 publications
5
94
0
6
Order By: Relevance
“…In addition, IPMK inhibition was also lethal for intracellular T. cruzi amastigotes, demonstrating the potential value of this drug target in T. cruzi. This extends the short list of validated targets for drug development in T. cruzi , which includes cytochrome b, cruzain, sirtuins and sterol 14α-demethylase (Doyle, et al, 2010; Khare, et al, 2015; McGrath, et al, 1995; Moretti, et al, 2015). Some IPMK inhibitors are also effective against P. falciparum , suggesting that these inhibitors may be broadly used to develop new antiparasitic drugs.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, IPMK inhibition was also lethal for intracellular T. cruzi amastigotes, demonstrating the potential value of this drug target in T. cruzi. This extends the short list of validated targets for drug development in T. cruzi , which includes cytochrome b, cruzain, sirtuins and sterol 14α-demethylase (Doyle, et al, 2010; Khare, et al, 2015; McGrath, et al, 1995; Moretti, et al, 2015). Some IPMK inhibitors are also effective against P. falciparum , suggesting that these inhibitors may be broadly used to develop new antiparasitic drugs.…”
Section: Discussionmentioning
confidence: 65%
“…Resveratrol can stimulate yeast Sir2 and its mammalian ortholog Sirt1 (Howitz et al., 2003) but can also affect other targets that might be contributing to the effects observed (Valera Vera et al., 2016, Harikumar and Aggarwal, 2008). Moreover, the effect of resveratrol described in this study can be only partially compared with the effects observed in parasites over-expressing sirtuins (Ritagliati et al., 2015, Moretti et al., 2015), further supporting the notion that targets other than sirtuins might be also responsible for its trypanocidal action. Resveratrol is a natural occurring phytoalexin found in the skin of red grapes, originally reported as a potential anticancer agent (Jang et al., 1997, Boocock et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC1 and 3 are essential for viability, while HDAC4 is required for normal cell cycle progression (Ingram and Horn, 2002). Coding sequences for HDACs have also been found in T. cruzi (El-Sayed et al., 2005), but only sirtuins deacetylases have been recently characterized (Ritagliati et al., 2015, Moretti et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Trypanosoma cruzi (Tc) has two sirtuins, TcSir2rp1 and TcSir2rp3. TcSir2rp1 was shown to be highly expressed in replicative parasite forms (epimastigotes and amastigotes) and less in metacyclic trypomastigotes and trypomastigotes derived from infected mammalian cells, while TcSir2rp3 was largely expressed in epimastigotes and cell-derived trypomastigotes, and much less in intracellular amastigotes and metacyclic trypomastigotes [37]. …”
Section: Discussionmentioning
confidence: 99%